2020
DOI: 10.1071/py19148
|View full text |Cite
|
Sign up to set email alerts
|

Universal access to oral health care for Australian children: comparison of travel times to public dental services at consecutive census dates as an indicator of progressive realisation

Abstract: Progressive realisation of equitable access to health services is a fundamental measure of a state’s resolve to achieve universal health coverage. The World Health Organization has reprioritised the importance of oral health services as an integral element of the roadmap towards health equity. This study sought to determine whether there is an indication of progressive realisation of equitable spatial access to public dental services for Australians <18 years of age through a comparison of travel times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Dental visit waiting-time [ 41 ] and applying virtual services and telehealth [ 38 , 42 ] may affect the availability of services and, consequently, access dental services in different ways. Geographical access, travelling time [ 43 ] and public transportation utilisation [ 44 ] are other determinants of physical access.…”
Section: Resultsmentioning
confidence: 99%
“…Dental visit waiting-time [ 41 ] and applying virtual services and telehealth [ 38 , 42 ] may affect the availability of services and, consequently, access dental services in different ways. Geographical access, travelling time [ 43 ] and public transportation utilisation [ 44 ] are other determinants of physical access.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two articles, published between 2010 to 2022, focused on accessibility to public and private dental practices, dental hospitals, and distribution of the dental workforce [ 29 , 30 , 41 , 48 , 52 , 57 – 61 , 65 , 71 , 80 , 86 90 , 96 , 101 , 106 , 107 ]. Articles focused on specific target populations, including paediatric [ 30 , 59 ], > 65 years [ 61 , 86 ], economically disadvantaged [ 41 ], and rural, regional, or remote [ 48 , 60 , 87 , 96 ]. One article analysed dental services for people living with a disability and used the National Survey of Disability, Ageing and Carers to model the prevalence of disability [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…One article analysed dental services for people living with a disability and used the National Survey of Disability, Ageing and Carers to model the prevalence of disability [ 71 ]. Sixteen articles accounted for socio-economic status (SES), seven used the ABS Socio-Economic Indexes for Areas (SEIFA) [ 30 , 80 , 88 90 , 96 , 106 ], and nine articles further specified the index used; for example, the Index of Relative Socio-economic Disadvantage (IRSD) [ 29 , 52 , 57 59 , 61 , 65 , 86 , 87 ]. Five articles used standardised geographic classification systems to define remoteness areas, including ARIA + [ 57 60 ] and the ABS ASGS-RA [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jean et al [ 57 ], who studied the travel time for dental care in socioeconomically disadvantaged groups living in remote communities, and Cao et al [ 58 ], who reported the travel time for access to preventive dental care, showed that the lower the group, the greater the travel time. Seo et al [ 59 ] reported that the NHI dental policy benefited the out-of-pocket spending of low-income households and the elderly.…”
Section: Discussionmentioning
confidence: 99%